2016
DOI: 10.5423/ppj.oa.03.2016.0063
|View full text |Cite
|
Sign up to set email alerts
|

Stemphylium Leaf Blight of Garlic (Allium sativum) in Spain: Taxonomy and In Vitro Fungicide Response

Abstract: The most serious aerial disease of garlic is leaf blight caused by Stemphylium spp. Geographical variation in the causal agent of this disease is indicated. Stemphylium vesicarium has been reported in Spain, whereas S. solani is the most prevalent species recorded in China. In this study, Stemphylium isolates were obtained from symptomatic garlic plants sampled from the main Spanish production areas. Sequence data for the ITS1–5.8S–ITS2 region enabled assignation of the isolates to the Pleospora herbarum compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
13
0
1
Order By: Relevance
“…Also, the results indicated that all fungicides inhibited the growth of both fungi C. oxysporum and C. lunata (100%), while they inhibited the growth of A. alternata in a percent of 81.1% with significant differences between them. This study agreed with Chatidimopoulos & Pappas (2016) and Gálvez et al (2016) who found that the fungicide Ortiva inhibited the growth of pear leaves spot disease caused by Septoria pyricola and garlic leaves spot disease caused by Stemphylium sp. This result was also in agreement with Al-Zubaidi (2005) who found that the fungicide Topas was one of the best fungicides using for inhibition the growth of date palm leaves spot pathogens.…”
Section: Effect Of Some Fungicides On the Growth Of Fungi Caused Eggplant Leaf Spot On Pdasupporting
confidence: 92%
See 1 more Smart Citation
“…Also, the results indicated that all fungicides inhibited the growth of both fungi C. oxysporum and C. lunata (100%), while they inhibited the growth of A. alternata in a percent of 81.1% with significant differences between them. This study agreed with Chatidimopoulos & Pappas (2016) and Gálvez et al (2016) who found that the fungicide Ortiva inhibited the growth of pear leaves spot disease caused by Septoria pyricola and garlic leaves spot disease caused by Stemphylium sp. This result was also in agreement with Al-Zubaidi (2005) who found that the fungicide Topas was one of the best fungicides using for inhibition the growth of date palm leaves spot pathogens.…”
Section: Effect Of Some Fungicides On the Growth Of Fungi Caused Eggplant Leaf Spot On Pdasupporting
confidence: 92%
“…This result was in agreement with Willis & Mavuso (2007) who mentioned that the fungicide Ortiva was very effective against avocado leaf spot caused by Pseudocercospora purpurea. Also, it was found that Ortiva can be used against garlic spot disease (Gálvez et al, 2016). Rohini et al (2015) found that the fungicide Carbendazim 50% gave the highest percentage of eggplant leaf spot disease protection.…”
Section: Effect Of Some Fungicides On Disease Severity Of Eggplant Leaf Spot Diseasementioning
confidence: 99%
“…Fungal contamination can be a problem when working with seeds and seedlings, especially after high humidity storage. To discard samples that show fungal contamination on DNA extracts, we tested for PCR amplification products of fungus-specific DNA regions using the internal transcribed spacer (ITS) region of the ribosomal DNA repeat cluster, as well as markers for the specific detection of three fungi genera commonly found in seeds: Fusarium , Penicillium , and Aspergillus (Gálvez et al, 2016; Gil-Serna et al, 2016). The universal primer pair ITS1-ITS4 was tested (5′-TCCGTAGGTGAACCTGCGG-3′ for ITS1 and 5′TCCTCCGCTTATTGATATGC-3′) for ITS4 (White et al, 1990) and other markers specific included an elongation factor specific for Fusarium (5′-ATGGGTAAGGAGGACAAGAC-3′/5′-GGAAGTACCAGTGATCATGTT-3′) (O'Donnell et al ., 1998) and betatubuline-specific for Penicillium and Aspergillus (5′-GGTAACCAAATCGGTGCTGCTTTC-3′/5′-ACCCTCAGTGTAGTGACCCTTGGC-3′ respectively) (Glass and Donaldson, 1995).…”
Section: Methodsmentioning
confidence: 99%
“…The quantity and quality of the extracted DNA were assessed using a BioSpectrometer (Eppendorf, Hamburg, Germany). The ITS region was amplified with the primers ITS1 (5′-TCCGTAGGTGAACCTGCGG-3′) and ITS4 (5′-TCCTCCGCTTATTGATATGC-3′) in a 20-μl reaction mixture using Pfu polymerase (Gálvez et al, 2016) (Elpis, Daejeon, Korea). DNA sequencing was performed by Macrogen Inc. (Daejeon, Korea).…”
mentioning
confidence: 99%